Afectividad y estrés laboral. - Silvestre Guamán, Luis Andrés (2015)
The objective of this work is to establish the types of affective reactions of the children before the absence of fathers by work-related stress, in a study conducted by López, Fernández, Prieto, Alcantara, Castro and Lopez (2012) point out that in traumatic situations children reach negative reactions with symptoms such as anxiety, depression, problems of the dreams or in turn also as aggression, hyperactivity, irritability, anger and even combine these aspects enfocandome in the rational emotive therapy of Ellis, establishing their irrational ideas and transforming them into rational with positive affective stimuli, the importance that has the affectivity emotional in the children. Indicating a methodical explanation qualitative descriptive type which describes the situations and events for the case analysis, with biographical and analytical methods, through the use of reagents and instruments, interviews, observation techniques, anamnesis and reactive psychological. Showing a result that determine that the emotional reactions of children by absence of fathers by occupational stress reflects the loss of spontaneity, repressing the affection she needs (sadness, anger, rejection, heartbreak) this prevails as a process for the emotions. Concluding that the emotional reactions of children are conditioned and effects may occur such as anger, aggressiveness insulation and disinterest as also a loathing toward the Father and to a long-term end in a problem of personality reaching negative reactions with symptoms such as anxiety, depression, or in turn also as aggression, hyperactivity, irritability, anger, and sometimes combine these aspects. It is recommended that a therapeutic work for the girl with a focus on rational emotive therapy and at the same time the family take therapies for the systemic approach to integrate the affectivity and regulate emotions and it is important to establish the emotional state of the children and to determine the degree of conflict with specialist to prevent future serious psychological problems.